Organization of individual work as a form of educational process at higher educational institutions for developing foreign language professional communication of students aquiring specialties connected with the transport industry - Makoviei, R. H.; Маковєй, Р. Г.; Маковей, Р. Г. (Харьковский национальный автомобильно-дорожный университет, 2018)
Problem. In recent years, the interest towards the independent work in organizing the educational process in all courses of studying a foreign language at institutions of higher education has increased significantly. Considerable attention is paid to the issues of upbringing the per-sonality of a modern specialist, one’s competitiveness, and public responsibility. Goal. The goal of the article is to determine the specifics of independent work as an important form of the main direction and tasks of the educational process at the university for the development of foreign language professional communication of students of transport specialties. Methodology. Analy-sis of the problem of organizing the independent work as a form of educational process at insti-tutions of higher education for the development of foreign language professional communica-tion of students of transport specialties was conducted. There was accomplished the analysis of recent researches of scientists and it was revealed that the problem of organizing the independ-ent work of students is prioritized and is expected to facilitate the revision of both the theoretical and methodological principles of modern training of competitive foreign language specialists. Results. It was established that the properly organized independent work of students of transport specialties increases the efficiency of management, control and self-control by independent work; improves the cognitive activity of students; develops their logical and creative thinking of the concepts of the language being studied; forms a conscious attitude to the outside world and stimulates the interest in the originality of thinking in a foreign language. Originality. The au-thor proposed the stages of organizing the independent work on the development of foreign lan-guage professional communication of students of transport specialties. Practical value. A com-petently organized independent work on foreign languge professional communication forms a foreign language communication competence, skills and abilities that ensure the acquisition of linguistic means, the definition of the communicative content of the understanding of individual linguistic units, their meanings, forms and structures, as well as the relationship between them.
Організація самостійної роботи як форми навчального процесу у ВНЗ для розвитку іншомовного професійного мовлення студентів транспортних спеціальностей
Организация самостоятельной работы как формы учебного процесса в ВУЗе для развития иноязычной профессиональной речи студен-тов транспортных специальностей
Keywords: independent work; modern specialist; educational process; higher education; specialized discipline; vocational training; professional skills; non-philology specialties; самостійна робота; розвиток іншомовного професійного мовлення; студенти транспортних спеціальностей; форми самостійної роботи студентів; етапи самостійної роботи студентів; самостоятельная работа; развитие иноязычной профессиональной речи; студенты транспортных специальностей; формы самостоятельной работы студентов; этапы самостоятельной работы студентов; 378.147:004